MENTORING AND EMPOWERMENT OF UNEMPLOYED YOUTH THROUGH SUPERIOR COUNTRY CHICKEN LIVESTOCK IN KEUTAPANG - Soraya Mashtura Hassan; Samsul Bahri; Asmaul Husna (ABDIMU: Jurnal Pengabdian Muhammadiyah, 2021)
Unemployed youth due to the Covid-19 pandemic continues to grow, this is a problem because youth are unemployed. This unemployment problem is very important to pay attention to because unemployment has the potential to cause various crimes (involved in narcotics) and social unrest, and poverty. Economic factors that are very worrying for unemployed youth are a problem in getting education and assistance as well as business capital in conducting superior free-range chicken farming. The method used in this service, the methods used in this counseling activity are: 1. Delivering the material that has been prepared with the question and answer method 2. After giving a motivational lecture to deepen the material that has been delivered, it is followed by a discussion on the care of superior free-range chickens 3. Giving business capital in the form of chicken seeds, feed vaccines and medicines for the treatment of superior native chickens, 4. provide training on how to ferment bran feed. The results obtained in this service are through mentoring, providing business capital and training for young people to have skills and knowledge about superior free-range chickens so that they can reduce the number of unemployed by starting a business of raising superior free-range chickens and creating jobs for themselves. Upgrade. The conclusion in this service is that the process of empowering unemployed youth through training assistance and business capital can improve their economic standard and quality of life by pioneering the business of raising superior free-range chickens and being able to assist other youths in raising superior free-range chickens.Keywords: Empowerment, Unemployed Youth, Superior Village Chicken